Anomalous temperature dependence of near‐infrared photoluminescence band in neutron‐irradiated α‐Al2O3. Issue 7 (26th March 2014) - Rahman, Abu Zayed Mohammad Saliqur; Wei, Long; Yang, Tao; Xu, Qiu; Atobe, Kozo
<x xml:space="preserve">Abstract</x> The properties of near‐infrared (NIR) photoluminescence (PL) spectra in a range of 0.8–2.8 μm in fast neutron‐irradiated α‐Al2O3 are reported. Anomalous temperature dependence of NIR PL spectra was observed in neutron‐irradiated α‐Al2O3 for the first time. Highest PL intensity was measured at 260 K whereas the intensity at low temperatures below 220 K decreased significantly. Phonon‐assisted indirect radiative recombination may be responsible for PL intensity enhancement at near room temperature. NIR PL band in a range of 0.8–2.8 μm may be well suited for application in broadly tunable color‐center laser because of its enhanced PL intensity at near room temperature. <inline-graphic xlink:href="ark:/27927/pghqcgq7q5" content-type="pssa201330660-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />